2016
DOI: 10.1177/8756479316634320
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Ultrasound-Guided Fine-Needle Aspiration Cytology by Cytopathologists in the Diagnosis of Major Salivary Gland Tumors

Abstract: Because of the typical sonographic appearances of many salivary gland masses, as well as the normal appearance and anatomy of the glands, differentiation of salivary glands tumors based only on clinical and imaging criteria is difficult. We compared the utility, safety, specificity, and accuracy of ultrasound-guided fine needle aspiration cytology (UG-FNAC) in the detection of nonpalpable tumors in the major salivary glands. A retrospective review was done of a 5-year experience of 102 consecutive patients und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…It is a limited diagnostic tool used as an initial, relatively noninvasive procedure when the clinical and radiographic features do not suggest an advanced disease [ 68 ]. The technique aims to examine the nature and origin of the cells inside the lumen of the cystic lesion and can either be performed as a simple biopsy under local anesthesia when the cystic lesion is superficial or easy to access or under regional or general anesthesia with ultrasound guidance, ultrasound-guided FNAC [ 69 ]. Tummidi et al [ 70 ] reported a case of sinonasal adenoid cystic carcinoma (SNACC) that was successfully diagnosed using FNA cytology alone.…”
Section: Resultsmentioning
confidence: 99%
“…It is a limited diagnostic tool used as an initial, relatively noninvasive procedure when the clinical and radiographic features do not suggest an advanced disease [ 68 ]. The technique aims to examine the nature and origin of the cells inside the lumen of the cystic lesion and can either be performed as a simple biopsy under local anesthesia when the cystic lesion is superficial or easy to access or under regional or general anesthesia with ultrasound guidance, ultrasound-guided FNAC [ 69 ]. Tummidi et al [ 70 ] reported a case of sinonasal adenoid cystic carcinoma (SNACC) that was successfully diagnosed using FNA cytology alone.…”
Section: Resultsmentioning
confidence: 99%